The 33 [videorecording (DVD)] - Banderas, Antonio; Santoro, Rodrigo, 1975-; Binoche, Juliette, 1964-; Brolin, James, 1940- (Warner Home Video, 2016)
In 2010, the eyes of the world turned to Chile, where 33 miners had been buried alive by the catastrophic explosion and collapse of a 100-year-old gold and copper mine. Over the next 69 days, an international team worked night and day in a desperate attempt to rescue the trapped men as their families and friends, as well as millions of people globally, waited and watched anxiously for any sign of hope.